Interventions for Preventing Cardiotoxicity in Breast Cancer Patients Receiving Trastuzumab: A Systemic Review and Bayesian Network Meta-Analysis - Li, Xinyi; Wu, Ziyang; Du, Xin; Wu, Yibo; Xie, Xiaohui; Shi, Luwen (Frontiers in Pharmacology, 2021)
Abstract Background Trastuzumab is associated with a risk of cardiotoxicity. Here we aim to explore interventions for preventing trastuzumab-related cardiotoxic effects in breast cancer patients. Methods Systematic review was performed including trials of breast cancer patients with intervention to prevent cardiotoxicity about trastuzumab. Trials were searched through databases including PubMed, Embase, Cochrane library. Results Eight RCTs were included. Five trials reported the outcomes of short-duration interventions, including 6-month and 9-week duration, and only 9-week treatment has significant difference compared with 12-month group (OR 0.38; 95 % CI 0.18 to 0.83) using cardiotoxicity as outcome. However, 6-month treatment turned to yield less occurrence of trastuzumab discontinuation (OR 0.32; 95 % CI 0.24 to 0.42). Three trials reported interventions of cardioprotective drugs, and there is no significant difference shown in any cardioprotective group compared with placebo (cardiotoxicity outcome: angiotensin converting enzyme inhibitor: OR 0.48; 95 % CI 0.057 to 2.3; angiotensin receptor blocker: OR 1.3; 95 % CI 0.12 to14; β-blocker: OR 0.48; 95 % CI 0.057 to 2.3; trastuzumab interruptions outcome: angiotensin converting enzyme inhibitor: OR 0.45; 95 % CI 0.12 to 1.3; angiotensin receptor blocker: OR 0.87; 95 % CI 0.15 to 4.8; β-blocker: OR 0.41; 95 % CI 0.11 to 1.2). Conclusion Only 9-week group has significant difference with 12-month group using cardiotoxicity as outcome. And 6-month treatment turned to yield less occurrence of trastuzumab discontinuation. The use of cardioprotective drugs failed to prevent trastuzumab-related cardiotoxic effects in breast cancer patients.